Teachers' perception of using geogebra in teaching mathematics in Malaysia - Shahmohammadi, Soheila Belgheis (2014)
This quantitative study examined Malaysian teachers’ perception towards using GeoGebra in the teaching of mathematics. The relationship between teachers’ Perceived Current Competencies (PCC) of GeoGebra, and Intention to Use (IU) it as well as the difference between male and female teachers and between users and non-users of GeoGebra were investigated. To collect data, an online survey among 132 teachers who had already participated in GeoGebra workshops was employed. The results of correlation and independent t-test revealed a positive relationship between teachers’ perceived current competencies with their intention to use GeoGebra in the teaching of mathematics. It also determined that there was no significant difference between male and female teachers in their intention to use GeoGebra while a significant difference between users and non-users of GeoGebra was observed.